Colorito sacro. Wątki biblijne w operze osiemnastego i dziewiętnastego wieku - MÜNCH, Stefan (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Biblical subject matter has been an important source for opera authors since the advent of this genre. The vertical dimension of culture, as well as the ubiquity of reference to the biblical motifs in literature, painting, theatre, and in the other musical genres, made opera authors naturally draw on this most universal cultural code. Indeed, the earliest theatrical creations, such as liturgical dramas, mystery plays and miracle plays, consisted in dramatizations of biblical scenes, not infrequently enriched with music. Elaborate Passion plays enjoyed a widespread popularity, yet their further evolution was impossible since their immediate reference to the New Testament prevented the authors from incorporating motifs from other sources (with the exception of the apocryphal Gospels). The movement of the Florentine Camerata, which resulted in the creation of the genre of opera on the threshold of the 17th century, was motivated by the intention to improve the art of music by returning to the Greek tragedy in its possibly original shape. Thus initially it was mythological and ancient themes that prevailed. The first operas based on the Bible appeared only in late 17th century in Germany. In Italy, however, it was not the opera, but the oratorio that demonstrated the strongest connection to the Biblical subject matter and was used for the purposes of enhancing piety. While the teachings of the Council of Trident ordered that particular arts be inspired by the Holy Scripture and thus preserve fidelity to the doctrine, the epic (narrative) character of numerous Books of the Bible was the reason why the part of the narrator provided the structure of the musical form. A vast majority of operas drawing on Biblical themes referred to Books of the Old Testament (e.g. Charpentier’s David et Jonathas, Monteclair’s Jephté, Rossini’s Mosè in Egitto, Verdi’s Nabucco, Gounod’s La reine de Saba and others). On the other hand, Hérodiade by Massenet, which draws on the Gospel, exemplifies the difficulties encountered by librettists, who continuously dodged between the Biblical narrative and the existing theatrical practice which prompted their use of the established theatrical means conforming to the expectations of the audiences. Not infrequently did the tendencies to include a romance motif, to introduce impressive crowd scenes or to accord with the lieto fine tradition turn out stronger than the intention to remain faithful to the Biblical message. Moreover, librettos often concerned the events the Holy Scripture describes only in a condensed way, focusing on the most important characters and on the unambiguous motivation of their actions. Thus the librettist, forced to provide enough text to «fill in» from three up to five acts of the opera, would retain the main Biblical plot, but he would simultaneously introduce numerous secondary themes and peripheral or episodic characters not present in the original Biblical source and endow his characters with additional motivations. In order to accomplish this task numerous means already used in the operatic theatre were employed, as well as those that conformed to the existing aesthetics of the spectacle, among them: stage effects, scene−painting techniques, choral and ballet scenes, the virtuosity of the singers, and a wide range of contrasting means of expression. Translated by Dorota Chabrajska